A Behavioral Analysis Behind the Intention to Adopt Islamic Financial Products and Services in Malaysia: Underpinning Social Cognitive Theory - Zulfaka, Auni; Kassim, Salina (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2025)
The growing global Muslim population and the increasing demand for halal products have also spurred interest in Islamic financial services, where the interplay between sacred and profane influences consumer choices. However, the market share of Islamic banking in Malaysia is still overshadowed by conventional banking, with only 33.4% of total deposits in 2018 attributed to Islamic banks. This indicates a significant challenge in attracting customers, where psychological factors play crucial roles in influencing behavioral intentions to adopt Islamic banking services. The study attempts to discover and provide an understanding on the ‘determinants factors on intention to adopt Islamic financial products and services with the integration of Social Cognitive Theory, Islamic financial literacy and the financial behavior of the consumer in Malaysia’. Partial Least Square PLS-SEM technique is used to analyze the 363 data in order to provide statistical result from respondents in the Klang Valley. The results demonstrate that all variables tested in this study have a strong relationship and identified as the determinants of intention to adopt Islamic financial products and services. The result from this study also provides practical implication for Islamic finance institutions to produce and market their Islamic financial products in the right and targeted market group.